Proposing a New Method for the Construction of Optimal Pairwise Balanced Block Designs Based on 3\(^n\) Symmetrical Factorial Design - Rajarathinam Arunachalam (Mathematics and Computer Science: Research Updates Vol. 3, 2025)
The concept of PBBD is merely the combinatorial interest in block designs. Because with the help of PBBD many other incomplete block designs can be constructed. This study proposed a new method for constructing Optimal Pairwise Balanced Block Design using the concept of 3n symmetrical factorial design has been proposed. The designs constructed using the proposed new method is satisfied A-Optimality, D-Optimality and E-Optimality criteria’s. The constructed method is illustrated with numerical example and the design is found to be universal optimal.